Isolation of Secondary Metabolites of Zingiberaceae Rhizomes by Spectrofotometry and Chromatography: A Review - Supartiningsih, Supartiningsih; Mairani, Fridelly; Putri, Ananda Dwi; Panggabean, Indah Elsayanti; Situmorang, Imelda Stefani Overia; Erni, Erni; Marbun, Eva Diansari (NSMRJ: Nusantara Scientific Medical Research Journal, 2025)
The Zingiberaceae family, known as the ginger family, is rich in secondary metabolites that contribute to its extensive use in traditional and modern medicine. Understanding effective methods for isolating these metabolites is crucial for advancing their pharmaceutical and nutraceutical applications. A literature review of 10 journal articles published between 2015 and 2025 was conducted. The focus was on spectrophotometric (UV-Vis, FTIR) and chromatographic (TLC, HPLC, LC-MS) techniques applied to the rhizomes of Zingiberaceae species. Data on compound identification, quantification, and method performance were analysed. Rhizomes of Curcuma aeruginosa, Alpinia purpurata, Zingiber officinale, and Boesenbergia pandurata were reported to contain flavonoids, alkaloids, phenolics, terpenoids, and curcuminoids. Spectrophotometric methods provided functional group identification and estimation of total metabolite concentrations. Chromatographic approaches enabled separation, purification, and structural elucidation with high specificity. Notably, flavenochromane C from Zingiber cassumunar and piperine from Alpinia purpurata were identified using LC-MS and NMR spectroscopy. In addition, TLC-densitometry for curcuminoids and xanthorrhizol in Curcuma xanthorrhiza demonstrated high accuracy and precision. Spectrophotometric techniques offer rapid and cost-effective screening, while chromatographic methods provide detailed identification and quantification of specific compounds. The complementary use of both approaches enhances the accuracy and reliability of isolating Zingiberaceae metabolites, supporting their further utilisation in medicinal research and product development.